Fabrication and Application of Enzyme-Incorporated Peptide Nanotubes - Yu, Lingtao (Bioconjug Chem, 2005)
Enzyme engineering is a fast-growing field in the pharmaceutical and food markets. For those applications, various substrates have been examined to immobilize and stabilize enzymes. In this report, we examined peptide nanotubes as supports for enzymes. When a model enzyme, Candida rugosa lipase, was encapsulated in peptide nanotubes, the catalytic activity of nanotube-bound lipases was increased 33% as compared to free-standing lipases at room temperature. At an elevated temperature, 65 °C, the activity of lipases inside the nanotubes was 70% higher than free-standing lipases. The activity enhancement of lipases in the peptide nanotubes is likely induced by the conformation change of lipases to the open form (the enzymatically active structure) as lipases are adsorbed on the inner surfaces of peptide nanotubes.